OBSERVATIONS ON THE EFFECT OF FERTILIZER AND FEED APPLICATIONS ON THE GROWTH OF PENAEUS INDICUS H. MILNE EDWARDS - Sivakami, S (Indian Journal of Fisheries, 2011)
Growth of Penaeus indicus in relation to phosphate fertilizer and feed applications was studied inmarine microcosms. The 1st dose of fertilizer did not appear to have any bearing on Chlorophyll-a andzooplankton production. An increase in sediment phosphate was obvious following addition of 1st doseof fertilizer in the treated pools. Shrimp production was the highest in pools treated with fertilizer andfeed and was the lowest in the control. Difference in shrimp growth among various treatments washighly significant except between control and the pools treated with feed alone.